2011
DOI: 10.1080/01430750.2011.584469
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance improvement of solar air flat plate collector: a theoretical analysis and an experimental study in Biskra, Algeria

Abstract: This article presents the results of the first experimental investigation of the performance of solar air flat plate collector at Biskra (latitude 34 48 0 N and longitude 5 44 0 E), Algeria. The thermal efficiency between absorber plate and air in flat plate solar collector has been enhanced by introducing obstacle rows in the dynamic air vein of the collector. For this objective, a flat plate solar collector, of 1.73 m 2 area and 25 mm air gap, has been designed and constructed. These obstacles formed with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
3
5
0
2
Order By: Relevance
“…It is noticed that the three curves have the same profile. This profile is similar to that of the instantaneous solar flux and that the variations in absorber temperatures are very sensitive with respect to its disturbances as reported by Vijayan and Arjunan [17] and Aoues et al [18]. The maximum value of the absorber temperature is observed as 83.6 °C, 91.3 °C and 95.4 °C for the first, second and third configuration of the flat plate solar collector, respectively during the peak sunshine hours, around 13 h. The highest absorber temperature was achieved by the third configuration of the flat plate solar collector, whereas the lowest value was obtained from the first configuration.…”
Section: Resultssupporting
confidence: 87%
“…It is noticed that the three curves have the same profile. This profile is similar to that of the instantaneous solar flux and that the variations in absorber temperatures are very sensitive with respect to its disturbances as reported by Vijayan and Arjunan [17] and Aoues et al [18]. The maximum value of the absorber temperature is observed as 83.6 °C, 91.3 °C and 95.4 °C for the first, second and third configuration of the flat plate solar collector, respectively during the peak sunshine hours, around 13 h. The highest absorber temperature was achieved by the third configuration of the flat plate solar collector, whereas the lowest value was obtained from the first configuration.…”
Section: Resultssupporting
confidence: 87%
“…Fig. 3 shows that the use of chicanes as artificial roughness influence significantly on the temperature field, as noted by Aoues et al [11], Mahboub et al [12]. For mass flow rate of 0.035 kg/s, it is observed that the air temperature increasing along the air stream dynamics length with a mean of (316.3 K) in the smooth case and with an average of (324.3 K, 329.5 K, 330.7 K and 332.1 K) in the case (without inclined part, 0°, 45° and 60°) with a rise of (2.52%, 4.17%, 4.55% and 4.99%)respectively.…”
Section: Reynolds Number Effect On the Heat Transfer Coefficientsupporting
confidence: 62%
“…For mass flow rate of 0.035 kg/s, it is observed that the air temperature increasing along the air stream dynamics length with a mean of (316.3 K) in the smooth case and with an average of (324.3 K, 329.5 K, 330.7 K and 332.1 K) in the case (without inclined part, 0°, 45° and 60°) with a rise of (2.52%, 4.17%, 4.55% and 4.99%)respectively. This is due to the secondary flow when it is trapped between two chicanes and the main flow where powered with a brewing phenomenon which provokes a heat transfer from the hot flow to the cold one, therefore the chicanes provide a delaying aspect for more and more time to the heat transfer process which is confirmed by Moummi et al [4][5][6][7][8][9][10][11][12][13]. …”
Section: Reynolds Number Effect On the Heat Transfer Coefficientsupporting
confidence: 53%
“…In addition, attention should be paid to the effective form of heatabsorbing solar energy. Currency, a large number of different forms of heat absorbents have been developed, often use fins, and V-shaped edges and matrix coating (Aoues, 2011;Razak, 2016). These coatings are quite effective compared to flat plate heat-absorbing plates, but they create a significant resistance to the flow of heat-carrier, which leads to the need to use a more powerful fan and renders such an inefficient coating for solar collectors with natural circulation.…”
Section: Introductionmentioning
confidence: 99%